Application of Sagnac Interferometer for Temperature Monitoring: Experimental Study - Omar, Mohd Azwadi; Cholan, Noran Azizan; Mohd Zawawi, Muhammad Alif Aiman; Jaharudin, Nurul Atika Nabila; Abd Rahim, Mohd Shahrir; Talib, Rahmat; Ngajikin, Nor Hafizah (Journal of Electronic Voltage and Application, 2020)
Temperature sensors have been widely used in industries and they have found applications in food processing units, medical devices, chemical handling processes, automotive and agriculture. In the market, there currently exist many varieties of temperature sensors including thermocouples, resistor temperature detectors, infrared sensor, thermistor, thermometer and optical temperature sensor. Of these technologies, optical temperature sensors have the edge in that they are free from electromagnetic interference, low weight, compact, high sensitivity, high signal-to-noise ratio and excellent stability. In this work, optical temperature sensor based on Sagnac interferometer is experimentally demonstrated. The Sagnac interferometer consists of a 3.5 cm polarization maintaining fiber that acts as a sensor head, a polarization controller and a 3 dB coupler. Experiments are carried out in which an amplifier noise being the input light for the Sagnac interferometer and the transmission spectrum of the output light is observed for the output. Throughout the experiment, the sensor head is placed in an oven for temperature variation. Based on the measurements on the output spectrum, it is found that the spectrum dips shifts to the shorter wavelength from 1554.96 nm to 1528.56nm as the temperature is varied from 30 °C to 45 °C. The spectrum dip is found to be inversely proportional to the temperature with the obtained sensitivity of 1.766 nm/°C. This Sagnac-based optical sensor is promising for detecting temperature especially in the harsh environment.